IoT-Based Automated Cabinet System for Drugs Storage and Accurate Retrieval for Operation Theater Application - Balachandran, Sivenesh; Mohd Shah, Shaharil (Journal of Electronic Voltage and Application, 2025)
Modern healthcare facilities, especially operation theaters, rely on a multitude of medications to ensure the well-being of patients during surgical procedures. In traditional operation theater environments, medications are typically stored in locked cabinets or storage units, with healthcare professionals manually retrieving and dispensing them as needed. This manual approach can be time-consuming, error-prone, and may lead to delays in urgent medical procedures. Thus, the development and implementation of an "IoT-Based Automated Cabinet System for Drugs Storage and Accurate Retrieval for Operation Theater Application” tailored for drug storage and retrieval in operation theaters becomes imperative and is proposed in this work. The system comprises three main components: a storage compartment system, a storage locking system, and a drugs retrieval system. These components are seamlessly integrated with an ESP32 Wi-Fi module and two Arduino Uno microcontrollers. In order, to enhance security, the automated cabinet system incorporates a three-level security feature. This includes AS608 fingerprint sensors and an S-60 electromagnetic lock, ensuring that only registered users can access the cabinet. The system leverages the Kodular application, which integrates with a Google Sheet Database for user authentication and administration. Experimental results demonstrate that it efficiently retrieves correct and substitute drugs, allowing healthcare professionals to monitor drug availability. In addition, it is shown that the HC-SR04 ultrasonic sensor system is efficient in tracking intended drugs within the storage compartment. The system also updates the remaining drug balance using Firebase Database, providing a reliable and efficient solution for operation theater applications. In a nutshell, by integrating various sensors and IoT technologies, this automated cabinet system significantly improves drug retrieval accuracy and efficiency, thereby enhancing patient safety and minimizing the risk of medication errors.